Bombyx mori U‐shaped regulates the melanization cascade and immune response via binding with the Lozenge protein. (13th October 2021) - Zhang, Kui; Tan, Juan; Hao, Xiangwei; Tang, Houyi; Abbas, Muhammad Nadeem; Su, Jingjing; Su, Yongyue; Cui, Hongjuan
Abstract: Zinc finger protein, an important transcription factor, regulates gene expression associated with various physiological and pathological processes. U‐shaped, belong to the Friend of GATA (FOG) transcription factor, plays a crucial role in hematopoiesis by interacting with the GATA transcription factor as a co‐factor. However, little is known about its functions in insects. In the present study, a U‐shaped cDNA was identified and characterized from the silkworm Bombyx mori and its potential roles in innate immunity investigated. The predicted silkworm U‐shaped amino acid sequence contained a classical nuclear localization signal (NLS) motif "GESSPKRRRR" at position 450–459, and arginine residues at position 456 and 478 are the critical sites of the NLS. U‐shaped mRNA was detected in all tested tissues of the B. mori ; however, the highest levels were found in the hemocytes. U‐shaped mRNA expression levels were upregulated in the hemocyte after the Escherichia coli and Staphylococcus aureus challenge. Furthermore, U‐shaped knockdown significantly reduced the melanization process and suppressed the expression of melanization‐associated genes, including PPO1, PPO2, PPAE and BAEE . In addition, U‐shaped interacts with Lozenge protein to regulate the innate immune response of the insect. Our results revealed that U‐shaped binds directly to Lozenge protein to modulate the melanization process and innate immune responses in silkworm. Abstract :